Chromatographic selectivity of graphene capillary column pretreated with bio-inspired polydopamine polymer1. Issue 90 (1st October 2015) - Han, Na; Qi, Meiling; Ye, Minghui; Fu, Ruonong; Qu, Liangti
<x xml:space="preserve">Abstract</x> Column fabrication by integration of graphene sheets on a polydopamine layer achieved improved column efficiency and chromatographic performance in capillary gas chromatographic separations.